Skip to content Skip to sidebar Skip to footer

Oct-Nov-21-p2-CIE-4037-22 : Solution







2021 (Oct-Nov) CIE (4037-Additional Mathematics), Paper 2/22 ၏ Question နှင့် Solution များ ဖြစ်ပါသည်။ Question Paper ကို Download ယူနိုင်ပါသည်။












  1. (a) On the axes, draw the graphs of $y=5+|3 x-2|$ and $y=11-x$.



    [4]








    (b) Using the graphs, or otherwise, solve the inequality $11-x < 5+|3 x-2|$.



    [2]




  2. SOLUTION
    $\begin{aligned}
    &y=5+|3 x-2| \\\\
    &y=3\left|x-\frac{2}{3}\right|+5 \\\\
    \therefore\ & \text { vertex }=\left(\frac{2}{3}, 5\right) \\\\
    &\text { When } x=0, y=7 \\\\
    \therefore\ & y \text {-intercept }=(0,7)\\\\
    &y=11-x\\\\
    &\text { When } x=0, y=11 \\\\
    \therefore\ & y-\text {-intercept } =(0,11)\\\\
    &\text { When } y=0, x=11 \\\\
    \therefore\ & x-\text {-intercept } =(11,0)\\\\
    \end{aligned}$





    According to the graph, the solution set to satisfy the inequality $1-x < 5+| 3 x-2|$ is $\{x \mid x <-2 \text { or } x>2\}$.




  3. (a) Expand $(2-3x)^4$, evaluating all of the coefficients.



    [4]




    (b) The sum of the first three terms in ascending powers of $x$ in the
    expansion of $(2-3 x)^{4}\left(1+\dfrac{a}{x}\right)$ is $\dfrac{32}{x}+b+c x$,
    where $a, b$ and $c$ are integers. Find the values of each of $a, b$ and $c .$



    [4]





  4. SOLUTION
    $\begin{aligned}
    (2-3 x)^{4} &=2^{4}+4\left(2^{3}\right)(-3 x)+6\left(2^{2}\right)(-3 x)^{2}+4(2)(-3 x)^{3}+(-3 x)^{4} \\\\
    &=16-96 x+216 x^{2}-24 x^{3}+81 x^{4} \\\\
    \end{aligned}$


    $\begin{aligned}
    (2-3 x)\left(1+\frac{a}{x}\right) &=\frac{32}{x}+b+c x+\cdots \\\\
    \left(16-96 x+216 x^{2}-24 x+81 x^{4}\right)\left(1+\frac{a}{x}\right) &=\frac{32}{x}+b+c x+\cdots \\\\
    16+\frac{16 a}{x}-96 x-96 a+216 a x+\cdots &=\frac{32}{x}+b+c x+\cdots \\\\
    \frac{16 a}{x}+(16-96 a)+(216 a-96) x+\cdots &=\frac{32}{x}+b+c x+\cdots \\\\
    \end{aligned}$


    $\begin{aligned}
    \therefore\ & 16 a =32, a=2 \\\\
    & b =16-96 a=-176 \\\\
    & c =216 a-96=336
    \end{aligned}$





  5. (a) Show that $\dfrac{1}{\sec x-1}+\dfrac{1}{\sec x+1}=2 \cot x \operatorname{cosec} x$.



    [4]




    (b) Hence solve the equation $\dfrac{1}{\sec x-1}+\dfrac{1}{\sec x+1}=3 \sec x$
    for $0^{\circ} < x < 360^{\circ}$.



    [4]


  6. SOLUTION
    $\begin{aligned}
    & \frac{1}{\sec x-1}+\frac{1}{\sec x+1} \\\\
    =&\ \frac{\sec x+1+\sec x-1}{(\sec x-1)(\sec x+1)} \\\\
    =&\ \frac{2 \sec x}{\sec ^{2} x-1} \\\\
    =&\ \frac{2 \sec x}{\tan ^{2} x} \\\\
    =&\ 2 \cdot \frac{1}{\cos x} \frac{1}{\tan x} \frac{1}{\tan x}\\\\
    =&\ \cdot \frac{1}{\cos x} \cdot \frac{\cos x}{\sin x} \cdot \cot x \\\\
    =&\ \frac{2}{\sin x} \cdot \cot x \\\\
    =&\ 2\cot x \operatorname{cosec} x\\\\
    \end{aligned}$


    $\begin{aligned}
    \frac{1}{\sec x-1}+\frac{1}{\sec x+1} &=3 \sec x, 0^{\circ}<x<360^{\circ} \\\\
    2 \cot x \operatorname{cosec} x &=3 \sec x \\\\
    2 \frac{\cos x}{\sin x} \frac{1}{\sin x} &=\frac{3}{\cos x} \\\\
    2 \cos ^{2} x &=3 \sin ^{2} x \\\\
    \tan ^{2} x &=\frac{2}{3} \\\\
    \tan x &=\pm \frac{2}{3} \\\\
    x &=39.2^{\circ} \text { or } \\\\
    x &=140.8^{\circ} \text { or } \\\\
    x &=219.2^{\circ} \text { or } \\\\
    x &=320.8^{\circ}
    \end{aligned}$




  7. (a) Find the $x$-coordinates of the stationary points on the curve
    $y=3 \ln x+x^{2}-7 x$, where $x>0$.



    [5]




    (b) Determine the nature of each of these stationary points.



    [3]





  8. SOLUTION
    $\begin{aligned}
    \text{(a) }\quad &y=3 \ln x+x^{2}-7 x \\\\
    &\frac{d y}{d x}=\frac{3}{x}+2 x-7 \\\\
    &\frac{d y}{d x}=0 \text { when, } \\\\
    &\frac{3}{x}+2 x-7=0 \\\\
    &2 x^{2}-7 x+3=0 \\\\
    &(2 x-1)(x-3)=0 \\\\
    &x=\frac{1}{2} \text { or } x=3\\\\
    \end{aligned}$


    $\qquad$ Hence, the curve has stationary points where $x=\dfrac{1}{2}$ or $x=3$.


    $\begin{aligned}
    &\\
    \text{(b) }\quad &\frac{d^{2} y}{d x^{2}}=-\frac{3}{x^{2}}+2\\\\
    &\text { When } x=\frac{1}{2}, \frac{d^{2} y}{d x^{2}}=-\frac{3}{\frac{1}{4}}+2=-10<0 \\\\
    &\text { When } x=3, \frac{d^{2} y}{d x^{2}}=-\frac{3}{9}+2=\frac{5}{3}>0\\\\
    \end{aligned}$


    $\therefore\quad$ The curve is maximum where $x=\dfrac{1}{2}$ and is minimum where $x=3.$




  9. (a) Solve the following simultaneous equations.


    $\begin{aligned}
    &\\
    \qquad e^{x}+e^{y}&=5 \\\\
    \qquad 2 e^{x}-3 e^{y}&=8
    \end{aligned}$




    [5]




    (b) Solve the equation $e^{(2 t-1)}=5 e^{(5 t-3)}.$



    [4]





  10. SOLUTION
    $\begin{aligned}
    \text{ (a) }\hspace{1.5cm} e^{x}+e^{y}&=5 \\\\
    e^{y} &=5-e^{x} \\\\
    2 e^{x}-3 e^{y}&=8 \\\\
    \therefore\ 2 e^{x}-3\left(5-e^{x}\right) &=8 \\\\
    2 e^{x}-15+3 e^{x} &=8 \\\\
    5 e^{x} &=23 \\\\
    e^{x} &=\frac{23}{5} \\\\
    x &=\ln \left(\frac{23}{5}\right) \\\\
    &=1.53\\\\
    e^{y} &=5-\frac{23}{5} \\\\
    &=\frac{2}{5} \\\\
    y &=\ln \left(\frac{2}{5}\right) \\\\
    &=-0.916\\\\
    \text{ (b) }\hspace{1.5cm}\frac{e^{(2 t-1)}}{e^{2 t-1}} &=5 e^{(5 t-3)} \\\\
    e^{5 t-3} &=5 \\\\
    \frac{1}{e^{3 t}-2} &=5 \\\\
    e^{3 t-2} &=\frac{1}{5} \\\\
    3 t-2 &=\ln \frac{1}{5} \\\\
    t &=\frac{1}{3}\left(2+\ln \frac{1}{5}\right) \\\\
    &=0.13
    \end{aligned}$



  11. DO NOT USE A CALCULATOR IN THIS QUESTION.



    All lengths in this question are in centimetres.


    You may use the following trigonometrical ratios.


    $\begin{aligned}
    &\\
    \qquad &\sin 60^{\circ}=\dfrac{\sqrt{3}}{2} \\\\
    \qquad &\cos 60^{\circ}=\dfrac{1}{2} \\\\
    \qquad &\tan 60^{\circ}=\sqrt{3}\\\\
    \end{aligned}$


    The diagram shows triangle $A B C$ with $A C=\sqrt{6}-\sqrt{2},
    A B=\sqrt{6}+\sqrt{2}$ and angle $C A B=60^{\circ}$.






    (a) Find the exact length of $B C$.




    [3]




    (b) Show that $\sin A C B=\dfrac{\sqrt{6}+\sqrt{2}}{4}$.




    [2]




    (c) Show that the perpendicular distance from $A$ to the line $B C$ is $1$.




    [2]



  12. SOLUTION
    $\text { (a) }$ By cosine Rule,


    $\begin{aligned}
    &\\
    \qquad BC^{2} &=A B^{2}+A C^{2}-2(A B)(A C) \cos A \\\\
    &=(\sqrt{6}+\sqrt{2})^{2}+(\sqrt{6}-\sqrt{2})^{2}-2(\sqrt{6}+\sqrt{2})(\sqrt{6}-\sqrt{2}) \cos 60^{\circ} \\\\
    &=6+2 \sqrt{12}+2+6-2 \sqrt{12}+2-2(6-2) \frac{1}{2} \\\\
    &=12 \\\\
    B C &=\sqrt{12} \\\\
    B C &=2 \sqrt{3}\\\\
    \end{aligned}$


    $\text { (b) }$ By Sine Rule,


    $\begin{aligned}
    &\\
    \qquad \frac{\sin (\angle A C B)}{A B} &=\frac{\sin (\angle B A C)}{B C} \\\\
    \sin (\angle A C B) &=\frac{A B}{B C} \sin (\angle B A C) \\\\
    &=\frac{\sqrt{6}+\sqrt{2}}{2 \sqrt{3}} \times \sin 60^{\circ} \\\\
    &=\frac{\sqrt{6}+\sqrt{2}}{2 \sqrt{3}} \times \frac{\sqrt{3}}{2} \\\\
    &=\frac{\sqrt{6}+\sqrt{2}}{4}\\\\
    \end{aligned}$


    $\text { (c) }$ Let $h$ be the perpendicular distance from $A$ to $B C$.


    $\begin{aligned}
    &\\
    \qquad \therefore\ h &=A C \sin (\angle A C B) \\\\
    &=(\sqrt{6}-\sqrt{2}) \frac{\sqrt{6}+\sqrt{2}}{4} \\\\
    &=\frac{6-2}{4} \\\\
    &=1
    \end{aligned}$



  13. It is given that $\dfrac{d^{2} y}{dx^{2}}=e^{2 x}+\dfrac{1}{(x+1)^{2}}$ for $x>-1$.



    (a) Find an expression for $\dfrac{dy}{dx}$ given that $\dfrac{d y}{dx}=2$ when $x=0$.



    [3]




    (b) Find an expression for $y$ given that $y=4$ when $x=0$.



    [3]



  14. SOLUTION
    $\begin{aligned}
    \frac{d^{2} y}{d x^{2}}=e^{2 x} &+\frac{1}{(x+1)^{2}}, x>-1 . \\\\
    \therefore \frac{d y}{d x} &=\displaystyle\int\left(e^{2 x}+\frac{1}{(x+1)^{2}}\right) d x \\\\
    &=\frac{1}{2} \displaystyle\int e^{2 x} d(2 x)+\displaystyle\int(x+1)^{-2} d x \\\\
    &=\frac{1}{2} e^{2 x}-\frac{1}{x+1}+c_{1} \\\\
    \frac{d y}{d x} &=2 \text{ when }x=0\\\\
    \frac{1}{2}-1+e_{1} &=2 \\\\
    c_{1} &=\frac{5}{2} \\\\
    \therefore\ \frac{d y}{d x} &=\frac{1}{2} e^{2 x}-\frac{1}{x+1}+\frac{5}{2}\\\\
    y &=\displaystyle\int\left[\frac{1}{2} e^{2 x}-\frac{1}{x+1}+\frac{5}{2}\right] d x \\\\
    &=\displaystyle\int \frac{1}{2} e^{2 x} d x-\displaystyle\int \frac{1}{x+1} d x+\frac{5}{2} \displaystyle\int d x \\\\
    &=\frac{1}{4} e^{2 x}-\ln (x+1)+\frac{5 x}{2}+c_{2} \\\\
    y &=4 \text { when } x=0 \\\\
    \therefore\ \frac{1}{4}+c_{2} &=4 \\\\
    \therefore\ c_{2} &=\frac{15}{4}\\\\
    \therefore\ y&=\frac{1}{4} e^{2 x}-\ln (x+1)+\frac{5 x}{2}+\frac{15}{4}
    \end{aligned}$



  15. Variables $x$ and $y$ are such that when $\sqrt{y}$ is plotted against
    $\log _{2}(x+1)$, where $x>-1$, a straight line is obtained which passes
    through $(2,10.4)$ and $(4,15.4)$.



    (a) Find $\sqrt{y}$ in terms of $\log _{2}(x+1)$.



    [4]





    (b) Find the value of $y$ when $x=15$.



    [1]





    (c) Find the value of $x$ when $y = 25$.



    [3]



  16. SOLUTION
    $ \text{ (a) }\quad$ The straight line passes through the points $(2,10.4)$ and $(4,15.4)$.



    $\begin{aligned}
    &\\
    \qquad\therefore \text{ gradient } &=\frac{15 \cdot 4-10 \cdot 4}{4-2}\\\\
    &=\frac{5}{2}\\\\
    \end{aligned}$


    $\quad \therefore\ $ Equation of straight line is


    $\begin{aligned}
    &\\
    \quad \sqrt{y}-10.4 &=\frac{5}{2}\left(\log _{2}(x+1)-2\right) \\\\
    \sqrt{y} &=\frac{5}{2} \log _{2}(x+1)+5-4\\\\
    \text{ (b) }\quad \text{ When } x&=15,\\\\
    \sqrt{y} &=\frac{5}{2} \log _{2}(16)+5.4 \\\\
    &=\frac{5}{2}(4)+5.4 \\\\
    &=15.4 \\\\
    y &=237.16\\\\
    \text{ (c) }\quad \text{ When } y&=25,\\\\
    \sqrt{25} &=\frac{5}{2} \log _{2}(x+1)+5.4 \\\\
    \log (x+1) &=-0.16 \\\\
    x+1 &=2^{-0.16} \\\\
    x &=2^{-0.16}-1 \\\\
    &=-0.105
    \end{aligned}$




  17. (a) Find the equation of the normal to the curve $y=x^{3}+x^{2}-4 x+6$ at
    the point $(1,4)$.



    [5]




    (b) DO NOT USE A CALCULATOR IN THIS QUESTION.


    Find the exact $x$-coordinate of each of the two points where
    the normal cuts the curve again.



    [5]





  18. SOLUTION
    $\begin{aligned}
    \text{ (a) } \hspace{1.5cm}\text{ Curve } : y&=x^{3}+x^{2}-4 x+6\\\\
    \frac{d y}{d x} &=3 x^{2}+2 x-4 \\\\
    \left.\frac{d y}{d x}\right|_{(1,4)} &=3+2-4 \\\\
    &=1\\\\
    \therefore\ \text{ gradient of normal } &=-1\\\\
    \end{aligned}$


    $\qquad$ The equation of normal line at $(1,4)$ is


    $\begin{aligned}
    &\\
    \quad y-4 &=-1(x-1) \\\\
    y &=5-x\\\\
    \end{aligned}$


    $\text{ (b) } \quad$ At the point of intersection of normal and curve,


    $\begin{aligned}
    &\\
    \qquad x^{3}+x^{2}-4 x+6&=5-x \\\\
    x^{3}+x^{2}-3 x+1&=0\\\\
    \end{aligned}$


    $\begin{aligned}
    \qquad \text{ Let } f(x)&=x^{3}+x^{2}-3 x+1\\\\
    f(1) &=1+1-3+1 \\\\
    &=0\\\\
    \end{aligned}$


    $\therefore(x-1)$ is a factor of $f(x)$.


    $\begin{aligned}
    &\\
    \qquad &\text{ Let } f(x)=(x-1)\left(x^{2}+k x-1\right)\\\\
    &\therefore\ x^{3}+x^{2}-3 x+1=(x-1)\left(x^{2}+k x-1\right)\\\\
    \end{aligned}$


    $\begin{aligned}
    \qquad \text{ When } x =2,\quad &\\\\
    8+4-6+1 &=(2-1)(4+2 k-1)\\\\
    7&=3+2 k \\\\
    k&=2\\\\
    \end{aligned}$


    $\begin{aligned}
    \qquad \therefore\ (x-1)\left(x^{2}+2 x-1\right)&=0 \\\\
    (x-1)\left(x^{2}+2 x+1-2\right)&=0 \\\\
    (x-1)\left((x+1)^{2}-2\right)&=0 \\\\
    \therefore x-1=0 \text { or }(x+1)^{2}-2&=0 \\\\
    \therefore x=1 \text { or } x=-1 \pm &\sqrt{2}\\\\
    \end{aligned}$


    $\quad$ The normal cuts the curve again where
    $x=-1-\sqrt{2}$ and $x=-1+\sqrt{2}$






  19. (a) The first three terms of an arithmetic progression are $x, 5x-4$ and
    $8x+2$. Find $x$ and the common difference.



    [4]




    (b) The first three terms of a geometric progression are $y, 5y-4$ and $8y+2$.





    (i)) Find the two possible values of $y$.




    [4]




    (ii)) For each of these values of $y$, find the corresponding value of the common ratio.




    [2]


  20. SOLUTION
    $\text{ (a) }\quad x, 5 x-4$ and $8 x+2$ ane in an A.P.


    $\begin{aligned}
    &\\
    \quad\therefore \quad 5 x-4-x &=8 x+2-5 x+4 \\\\
    4 x-4 &=3 x+6 \\\\
    \therefore \quad x &=10\\\\
    \end{aligned}$


    $\qquad$Let the common difference be $d$.


    $\begin{aligned}
    &\\
    \quad\therefore\quad d &=5 x-4-x \\\\
    &=4 x-4 \\\\
    &=4(x-1) \\\\
    &=4(10-1) \\\\
    &=36\\\\
    \end{aligned}$


    $\text{ (b) }\quad y, 5 y-4$ and $8 y+2$ are in G.P.


    $\begin{aligned}
    &\\
    \text{ (i) }\hspace{1.5cm} \therefore \frac{5 y-4}{y} &=\frac{8 y+2}{5 y-4} \\\\
    \quad 25 y^{2}-40 y+16 &=8 y^{2}+2 y \\\\
    17 y^{2}-42 y+16 &=0 \\\\
    (17 y-8)(y-2) &=0 \\\\
    \therefore y=\frac{8}{17} \text { or } y &=2\\\\
    \end{aligned}$


    $\text{ (ii) }\quad$ Let the common ratio be $r$,


    $\begin{aligned}
    &\\
    \qquad\text{ When } y&=\frac{8}{17},\\\\
    r &=\frac{5 y-4}{y} \\\\
    &=\frac{5\left(\frac{8}{17}\right)-4}{\frac{8}{17}} \\\\
    &=-\frac{7}{2}\\\\
    \text{ When } y&=2,\\\\
    r &=\frac{5 y-4}{y} \\\\
    &=\frac{10-4}{2} \\\\
    &=3
    \end{aligned}$

Post a Comment for "Oct-Nov-21-p2-CIE-4037-22 : Solution"

Sponsored by: iklanvideo.io